Three phase DC-DC converter with six inverter for EV application - Alam, A. H. M. Zahirul; Che Mat, Zulaikha (Kyushu University, Japan, 2017)
This paper presents the effect of inductor and switching frequency of a three phase DC-DC converter for possible application in an electrical vehicle. The proposed DC-DC converter consists of the primary and secondary stage. The primary stage of the converter is composed of full bridge converter act as input port which connected in parallel, while at the secondary stage which acts as output port comprised of full bridge rectifier connected in series. At the secondary stage, filter capacitor, an inductor connected in parallel to filter out the ripples from the input voltage and produce a DC output voltage that leads to better performance. Different stages of the DC-DC converter has been simulated through PSpice and performance were evaluated.